Institutional Reform and the Consequences of 30-S - Falconí, Fander (2011)
The authors maintain that the events of September 30 constitute a coup attempt. This is a political fact that demonstrates that the change promoted by the Government has provoked resistance from some groups in Ecuadorian society. However, resistance and conflicts are the response to all change and institutional reform, whether neoliberal or, as in this case, postneoliberal, since said change affects the mechanisms of power and privilege of certain sectors. However, what is surprising is the degree of violence that these groups are prepared to foment in order to put an end to the reform process. From this observation, the authors propose a reflection on the event.